Donor site morbidity following radial forearm free flap reconstruction with split thickness skin grafts using negative pressure wound therapy - Jessica M. Clark; Shannon Rychlik; Jeffrey Harris; Hadi Seikaly; Vincent L. Biron; Daniel A. O’Connell (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Donor site complications secondary to radial forearm free flap (RFFF) reconstruction can limit recovery. Optimizing hand and wrist function in the post-operative period may allow more efficient self-care and return to activities of daily living. Negative pressure wound dressings (NPD) may increase blood flow and perfusion as compared to static pressure dressings (SPD) designed to minimize shear forces during the healing period. This study aims to compare subjective and objective hand and wrist functional outcomes following RFFF reconstruction with split thickness skin grafts (STSG) in patients treated with NPD and SPD. Methods Adult patients undergoing RFFF with STSG were identified preoperatively and randomized to receive NPD or SPD following their RFFF reconstruction. NPD involved a single-use, portable device capable of applying 80 mmHg of negative pressure to the forearm donor site. SPD involved a volar splint. Dressings were left in place for seven days with subjective and objective function assessed at seven days, one month and three months postoperatively. The primary outcome was self-reported hand function as measured with the function subscale of the Michigan Hand Questionnaire (MHQ). Secondary outcomes included hand and wrist strength, range of motion, sensation, scar aesthetics, and skin graft complications. Results Twenty-four patients undergoing RFFF were randomized to NPD or SPD. Patients treated with NPD had improved MHQ self-reported functional scores as compared to those treated with SPD at seven days postoperatively (P = 0.016). Flexion at seven days was improved in NPD group (P = 0.031); however, all other strength and range of motion outcomes were similar between groups. There were no differences in rates of graft complications, scar aesthetics, or sensation. Conclusions In the immediate post-operative period, NPD was associated with improved patient-reported hand and wrist function. Wound care to optimize hand and wrist function could allow for improved patient outcomes in the immediate postoperative period.